Affirmation of the rights and obligations of couriers in cash on delivery marketplace transactions - Ferynando, Hamka; Suryandari, Wieke Dewi; Tohari, Mohamad (Indonesian Journal of Multidisciplinary Science, 2024)
The Cash on Delivery (COD) payment scheme in Indonesia has become a popular choice in e-commerce, offering convenience and trust to consumers, particularly those without access to digital banking services. However, this scheme presents significant challenges, particularly for couriers who bear the brunt of operational and financial risks. Despite their role as intermediaries, couriers face unfair expectations, including bearing the costs of unpaid goods or managing buyer dissatisfaction over product non-conformity. This research examines the rights and obligations of couriers in COD transactions through a normative legal and case study approach. The findings reveal systemic gaps in legal protections and a lack of clear regulatory frameworks to safeguard couriers' rights, compounded by unfair corporate policies and limited awareness among couriers regarding their legal boundaries. To mitigate these challenges, the study recommends developing comprehensive legal frameworks, promoting good faith among transaction parties, and exploring innovative solutions such as integrating technology to enhance transparency and accountability. This study contributes to the legal and e-commerce fields by proposing actionable solutions to protect couriers while fostering a sustainable COD ecosystem. Future research should focus on comparative studies of international practices, the psychological impact on couriers, and alternative payment systems to address the inherent risks in COD transactions.